ANTISIPASI KERUGIAN KONSUMEN AKIBAT KLAUSULA BAKU DALAM PERJANJIAN PINJAMAN ONLINE - Devi Wulandari; Widya Agustina Siregar; Rizka Amelia Azis (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
Consumers and business actors often have an unequal position, resulting in losses for consumers, including the existence of standard clauses that cause these losses. The purpose of this study is to analyze the anticipated losses that consumers can incur due to standard clauses in agreements.online This study examines both short-term preventive measures and long-term repressive measures. The research was conducted using normative methods and legislative, conceptual, and case-based approaches. The data used were secondary data collected through literature review. The results indicate that short-term measures that consumers can take to avoid losses arising from standard clauses in loan agreements include:online is to ensure legality platform loan online to be registered with the OJK, identify standard clauses that have the potential to cause losses so that they can be sorted out platform which one presents the smallest risk, collecting electronic document evidence, not carelessly providing personal data that is not required, submitting an internal objection mechanism through call center platform loan online, and submit a proposal to the Business Competition Commission to correct the standard clauses in the agreement. Meanwhile, long-term efforts that consumers must take if they experience losses include filing an objection with the business actor to request information regarding the losses resulting from the standard clause. Consumers can then report this to the Financial Services Authority (OJK) so that the provider is subject to administrative sanctions and dispute resolution mechanisms stipulated in Law No. 8 of 1999, both non-litigation and litigation through criminal prosecution of the business actor. Finally, consumers can encourage the reconstruction of regulations that provide protection for consumers affected by the standard clause in loan agreements.online by submitting an application to the Constitutional Court.<line-break/>Keywords: standard clauses, agreements, loans online, loss, consumer